Peran Guru Pendidikan Agama Islam dalam Pembinaan Sikap Spiritual dan Sosial di Sekolah Menengah Pertama - Desi Karlina (Tadabbur: Jurnal Peradaban Islam, 2021)
Globalization has resulted in a shift in human morals, marked by the many cases of moral deviations that are rife in various parts of Indonesia so that the application of spiritual attitudes has not been maximized. The attitude of dishonesty is shown by the number of students who cheat on the test, and the attitude of indiscipline is shown by the number of students who are late so that the application of social attitudes does not seem to be visible. The role of PAI teachers is considered quite important for the development of these two attitudes. At SMPN 1 Darussalam, PAI teachers have played a role in fostering spiritual and social attitudes. Big. This research was conducted with a field study using a qualitative descriptive method. Data collection techniques were carried out through interviews and documentation. The results showed the role of PAI teachers in fostering spiritual attitudes by praying before and after lessons, praying in congregation, doing charity activities every Friday, and religious activities. The role of PAI teachers in fostering social attitudes is carried out through social service activities, visiting the Disabled Foundation and nursing homes, getting used to the 3S (smile, greeting, greeting), reporting to the teacher what items are found, punishing students who are late. Factors supporting the role of Islamic Education teachers in fostering spiritual and social attitudes are seen from adequate school facilities in the form of female/male prayer rooms, learning media such as LCD, the use of active methods. While the inhibiting factors include the lack of adequate facilities, especially LCDs, the lack of interest in teachers and knowledge, and the lack of interest in students to improve themselves.